Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

y = 3e 2x + 2e 3x ..prove that d 2 y/dx 2 – 5dy/dx + 6y =0

y = 3e2x + 2e3x..prove that d2y/dx2 –  5dy/dx + 6y =0

Grade:12

1 Answers

Adarsh
11 Points
3 years ago
Dy/DX=6e^2x+6e^3xD2y/dx2=12 e^2x+18e^3xSubstituting in the equation we get12e^2x+18e^2x-30e^2x+18e^3x+12e^3x-30e^3x=30e^2x-30e^2x+30e^3x-30e^3x=0.Hence proved

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free